Réponses

Meilleure réponse !
2014-05-27T20:55:38+02:00
E = (5x -4)(-3 +9x) - ( 3x -7)(6x+8)
E = (-15x +45x² +12 -36x) - ( 18x² +24x -42x -56)
E = (+45x² -51x +12) - ( 18x² -18x -56)
E = 45x² -51x +12 -18x² +18x +56
E = 27x² -33x +74

A = (3x +4)(2x +9) + ( 4x +2)(3x +6)
(6x² +27x +8x +36) + ( 12x² +24x +6x +12)
6x² +35x +36+ 12x² +30x +12
+18x² +65x +48

B= (5x -3)(2x+3) - ( x+2)(5 -x)
10x² +15x -6x -9) - ( 5x -x² +10 -2x)
10x² +9x -9 -(+3x -x² +10)
10x² +9x -9 -3x +x² -10
+11x² +6x -19

C = (4 -5x)(-x-7) - ( 2x -4)(3x-5)
(-4x -28 +5x² +35x) - ( 6x² -10 x -12x +20)
(+5x² +31x -28) - ( 6x² -22x +20)
5x² +31x -28 -6x² +22x -20
-x² +53x -18